(untitled) (Bangladesh Journal of Botany, 2026)
This study evaluated the effects of polyphenol-rich dietary fruits and vegetables on the oral microbial consortium of 20 volunteers. Methanol-ethanol extracts were prepared from the selected fruits and vegetables, and their antimicrobial activity was assessed against the prepared oral microbial consortium. Emblica officinalis fruit extract showed the largest inhibition zone, both the disc diffusion (17.7 mm) and agar well diffusion (18.4 mm) assays, followed by Ipomoea aquatica and Enhydra fluctuans at 2000 μg extract. E. officinalis and I. aquatica powders were also successively fractionated into n-hexane (Hex), chloroform (Chl), and finally methanol (Met) fractions. The strongest antimicrobial activity with 22 and 23 mm zone diameters was observed in the Chl fractions of E. officinalis and I. aquatica, respectively, followed by the Met fraction (19.6 mm) of E. officinalis at 1000 μg/well. The broth microdilution method revealed the minimum inhibitory concentration (MIC) of 4000 μg/ml for Chl and Met fractions. Therefore, E. officinalis and I. aquatica extracts, especially their Chl and Met fractions, can be incorporated as functional ingredients in mouthwash and toothpaste to manage oral microorganisms and associated hygiene. Bangladesh J. Bot. 55(1): 209-215, 2026 (March)